Comparative Physicochemical and Antioxidant Activities of Eight Commercially Available Antidiabetic Polyherbal Products (Nigerian Journal of Pharmaceutical Research, 2022)
Background: High cost and side effects of current drugs has led to increased use of herbal preparations for Diabetes Mellitus, which is a chronic multifactorial disease associated with several complications and more than 422 million people affected worldwide.Objectives: To comparatively evaluate physicochemical and antioxidant properties of eight commercially available antidiabetic polyherbal products.Material and methods: Samples were subjected to physicochemical analysis; organoleptic tests, uniformity of weight, thin layer chromatography (TLC), phytochemical screening, heavy metals, extractive values, moisture content, ash values, antioxidant activity using 1,1-diphenyl-2-picrylhydrazyl (DPPH) inhibition and total phenolic content (TPC). Statistical analysis was done at p < 0.05.Results: The samples which ranged from tablets, capsules to tea sachets were of varying colour, odour and taste, with obtained average weights significantly different from the labelled weight for most products The TLC analysis gave varied number of spots with the identified phytochemicals (tannins, flavonoids, phenols and proteins) confirmed by phytochemical screening. Moisture contents ranged from 5.99 to 8.84 %w/w, with water and alcohol-soluble extractives 13.0-27.7%w/w and 15.4-47.5 %w/w respectively. Lead, arsenic and cadmium contents were within WHO specification. Total ash, water-soluble ash and acid-insoluble ash ranged from 1.27 ±0.02 to 42.40 ±0.04; 0.36 ±0.01 to 37.65 ±0.05 and 0.29 ±0.02 to 7.10 ±0.03 %w/w respectively. The TPC ranged from 0.015 ±0.006 to 0.277 ±0.006 mgGAE/mL with DPPH scavenging activity (IC50) ranging from 8.87 ±0.113 to 825.24 ±2.03 µg/mL.Conclusion: Only two brands complied with all the WHO herbal products specifications, while varied antioxidant activities were observed across all the polyherbal products.
Keywords: Antidiabetic polyherbal products; Phytochemical screening; Antioxidant activity; DPPH inhibition; Total phenolic content